2017
DOI: 10.1055/s-0043-118538
|View full text |Cite
|
Sign up to set email alerts
|

Hybrids of Steroid and Nitrogen Mustard as Antiproliferative Agents: Synthesis, In Vitro Evaluation and In Silico Inverse Screening

Abstract: Hybrids of 16E-arylidene steroids and nitrogen mustard have been synthesized and evaluated for their in vitro cytotoxic activity to develop tissue specific antineoplastic agents from steroids. These hybrids displayed specificity towards leukemia cell lines, however somewhat reduced potency was observed in comparison with the earlier reported 16E-arylidene steroids. The in silico reverse screening experiments were employed to find out the probable pharmacological mechanism of these hybrids. Molecular docking st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Despite these promising results, other studies carried out with 2- and 16 E -arylideneandrostrane derivatives were described, but less relevant biological effects were observed [ 17 , 38 , 50 , 55 , 64 , 67 ]. In addition, Semenenko and coworkers prepared 16 E -arylidenedehydroepiandrosterones, as well as 2-arylidenesteroidal derivatives of cholestanone, to be used as chiral dopants for cholesteric liquid crystal composition [ 74 ].…”
Section: Bioactivity Of 2- and 16 E -Arylideneamentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these promising results, other studies carried out with 2- and 16 E -arylideneandrostrane derivatives were described, but less relevant biological effects were observed [ 17 , 38 , 50 , 55 , 64 , 67 ]. In addition, Semenenko and coworkers prepared 16 E -arylidenedehydroepiandrosterones, as well as 2-arylidenesteroidal derivatives of cholestanone, to be used as chiral dopants for cholesteric liquid crystal composition [ 74 ].…”
Section: Bioactivity Of 2- and 16 E -Arylideneamentioning
confidence: 99%
“…However, the specificity of these compounds towards leukemia cells still remains unaffected and reduced potency was observed when compared to earlier reports for 16 E -arylidene steroids [ 61 , 62 ]. Further studies suggested that these derivatives present different mechanisms of action in leukemia cells [ 17 ]. More recently, Brito et al reported the synthesis, antiproliferative effects, and in silico studies of novel 16 E -arylidene-4-azaandrost-5-enes as prostate cell growth inhibitors.…”
Section: Bioactivity Of 2- and 16 E -Arylideneamentioning
confidence: 99%
See 2 more Smart Citations
“…The search for a cancer chemotherapeutic agent with better efficacy and less toxicity endures a challenge for a new drug discovery process and has always compelled medicinal chemists to discover innovative agents with cancer selectivity . Isatin-inspired spirooxindole derivatives are a highly precious synthetic framework due to their diversified biological properties including the antiproliferative activity. , Spirooxindoles are found in several bioactive natural products such as coerulescine, horsfiline, spirotryprostatin A, welwitindolinone A, elacomine, and alstonisine .…”
Section: Introductionmentioning
confidence: 99%